Performance of Regional Development Planning Policy Through Development Plan Deliberation (Musrenbang) in the Framework of Optimizing Regional Autonomy - Ibrohim, Ibrohim; Ismanudin, Ismanudin (Gema Wiralodra, 2025)
The regional development planning policy carried out through Musrenbang according to the level of government has long been implemented. This research aims to find out the concept and performance of development planning policies through the Development Plan Consultation (Musrenbang) so far, as well as problems and solutions in the future. The research method used is descriptive method with qualitative approach through literature study. The results of the study indicate that the concept and performance of the implementation of regional development planning policies as a whole in order to produce an effective development implementation based on more adequate planning has not been achieved effectively. Implementation of regional development planning policies through Musrenbang is also still faced with a number of obstacles, both internal and external. This is related to factors such as socio-economic and technological conditions, less than optimal public support, attitudes and resources owned by the group, less than optimal support from the central government and regional governments themselves, as well as weak commitment and leadership abilities among several implementing officials at the regional level.